First results of a mixed plantation with high quality timber broadleaves and N-fixing trees - Buresti, Enrico (2018)
In 1985, an experimental plantation was established in Central Italy in order to verify the development of different broadleaves with high quality timber, (Fraxinus angustifolia, Juglans nigra, Prunus avium and Quercus robur). The stand were planted pure or mixed with different N-fixing trees (Alnus cordata, Robinia pseudoacacia, Ealeagnus angustifolia). Seven years after plantation, the results point out the positive effects of the mixtures on the main species growth pattern and also a growth difference according to the specific combinations. The different behaviour may be due to the different above-ground competition in the various mixture types (deppending on the height growth rate and crown arquitecture of each species) and also to the different bellow-ground competition (deppending on the root system morphology and nutrients cycling). In order to understand the effects of above-ground and bellow-ground competion, other researches will be developed